Developing social capital and community empowerment among the Malaysian youth through international youth exchange program with South Korea and Japan - Nabila Huda Ibrahim; Keum Hyun, Kim; Seung Yoan, Rou (Penerbit Universiti Kebangsaan Malaysia, 2023)
Social capital development is indispensable to economic growth and well-being because it allows individuals to contribute meaningfully to a society or community. The density of social networks helps an individual take ownership of control over their community through shared trust, norms, and values. As a component to human capital, social capital needs to be developed with important skills and knowledge, such as leadership, communication, and networking to pursue community empowerment. This study examines the development of social capital and community empowerment at the international level through the international youth exchange program (IYEP) under the Look East Policy (LEP). LEP was implemented in 1982 to develop human capital and increase bilateral collaboration and socio-cultural exchange with East Asian countries, i.e., South Korea and Japan. Based on the secondary data obtained from the Ministry of Youth and Sports and reports from related agencies, this study examined the IYEP of the Malaysia–South Korea and Malaysia-Japan programs and compared their impact on social capital and youth community empowerment. The findings indicate that the IYEP with both countries is expected to strengthen the partnership among participants and help nurture leadership skills. The focus was similar to sociocultural exchange and regional knowledge despite the different scales. Activities such as exchange of knowledge, discussions, enjoying cultural activities, and local activities help the participants build their networking skills and empower the community at both individual and group levels. As the IYEP has benefited its participants, it should be diversified in many areas and collaborations.